2020
DOI: 10.1128/aac.01956-19
|View full text |Cite
|
Sign up to set email alerts
|

Early Bactericidal Activity Trial of Nitazoxanide for Pulmonary Tuberculosis

Abstract: This study was conducted in treatment-naive adults with drug-susceptible pulmonary tuberculosis in Port-au-Prince, Haiti, to assess the safety, bactericidal activity, and pharmacokinetics of nitazoxanide (NTZ). This was a prospective phase II clinical trial in 30 adults with pulmonary tuberculosis. Twenty participants received 1 g of NTZ orally twice daily for 14 days. A control group of 10 participants received standard therapy over 14 days. The primary outcome was the change in time to culture positivity (TT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
41
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(46 citation statements)
references
References 18 publications
3
41
0
Order By: Relevance
“…NTZ was used as the reference level for treatment (see Methods and Supplementary Table S1) ( Figure 2B). NTZ, despite its potent in vitro activity27, did not have any significant effect on TTP after 14 days ( > 0.05) ( Figure 2B, Supplementary Table S1) 26 . This lack of NTZ efficacy was traced to a failure of the drug to penetrate the sputum, 26 and indicated that disease severity remained constant as measured by mycobacterial load.…”
Section: Resultsmentioning
confidence: 95%
See 3 more Smart Citations
“…NTZ was used as the reference level for treatment (see Methods and Supplementary Table S1) ( Figure 2B). NTZ, despite its potent in vitro activity27, did not have any significant effect on TTP after 14 days ( > 0.05) ( Figure 2B, Supplementary Table S1) 26 . This lack of NTZ efficacy was traced to a failure of the drug to penetrate the sputum, 26 and indicated that disease severity remained constant as measured by mycobacterial load.…”
Section: Resultsmentioning
confidence: 95%
“…Gut microbiome diversity is depleted after two weeks of HRZE or NTZ treatment As detailed elsewhere, the GHESKIO centers in Port au Prince, Haiti conducted a prospective, randomized, early bactericidal activity (EBA) study in treatment-naive, drug-susceptible adult patients with uncomplicated pulmonary tuberculosis (TB) (ClinicalTrials.gov Identifier: NCT02684240) 26 . Thirty-four participants were randomized to receive either NTZ, 1000 mg po (oral) twice daily, or standard oral therapy with isoniazid 300 mg daily, rifampin 600 mg daily, pyrazinamide 25 mg/kg daily, and ethambutol 15 mg/kg daily (referred to as HRZE) for 14 days ( Figure 1A).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…To independently validate our findings, we obtained and analyzed urine samples from a second cohort of 35 participants with ATB enrolled in an early bactericidal activity (EBA) study at the Groupe Haitien d'Etudes du Sarcome de Kaposi et des Infections Opportunistes (GHESKIO) Centers in Port-au-Prince, Haiti. The study was designed to determine if the in vitro activity of the FDA-approved antiparasitic agent nitazoxanide (NTZ) against Mycobacterium tuberculosis (Mtb) could serve as a mycobactericidal agent for drug-sensitive pulmonary TB (24). Participants were recruited at the GHESKIO Centers and allocated into 2 treatment arms: 19 participants received NTZ for 14 days, whereas 16 participants received the standard HRZE TB treatment ( Figure 1).…”
Section: L I N I C a L M E D I C I N Ementioning
confidence: 99%